Adding Celecoxib With or Without Zoledronic Acid for Hormone-Naïve Prostate Cancer: Long-Term Survival Results From an Adaptive, Multiarm, Multistage, Platform, Randomized Controlled Trial - John Wagstaff (Journal of Clinical Oncology, 2017)
In this multiform, multistage trial 1245 men with high risk locally advanced or metastatic prostate cancer were treated with standard of care hormone therapy (SOCHT) and randomised (2:1:1) to receive SOCHT alone, SOCHT plus celecoxib (cel) or SOCHT plus cele plus zoledronic acid (ZA). Prostate (+/- pelvic) radiotherapy was encouraged for men with localised disease. In the SOCHT arm median survival was 66 months. The hazard ratio for death in the SOCHT + cel arm was 0.98 (95% CI 0.80 to 1.20, median survival 70 months, p=0.847). The hazard ratio for death in the SOCHT + cel + ZA was 0.86 (95% CI 0.70 to 1.05, median survival 76 months, p=0.13). these data show no overall evidence of improved survival with cel.